Educação popular e redução de danos no campo das drogas - Silva, Ione Gomes da (2025)
Whether derived from a plant or produced in a laboratory, a drug is an inanimate substance. Its dangerous or beneficial potential only appears when a relationship is established between it and a living organism. Therefore, rationality tells us that the correct decision is to invest in educational approaches and humanised treatments, in other words, to educate human beings so that they learn to establish autonomous and balanced relationships with them, because it is impossible to eradicate drugs completely. In this sense, it is essential to take care to minimise the risks and damage that may eventually arise as a result of consumption. According to this perspective, the role that have been attributed to harm reduction in public policies is to take care to prevent the transmission of diseases and make consumption safer, without indicating abstinence as a goal to be achieved. In the context of this debate, Popular Education has been recognising as a critical educational conception that has focused on the field of drugs and harm reduction as new areas of its analysis and practices. In this way, Popular Education takes into account a historical reality that is different from its classical context, and dialogues with a group of heterogeneous actors who are exposed to different types of oppression, both as drug users and as members of dispossessed social sectors. This is the thematic area of this study, and its general objective is to analyse how Popular Education approaches have been including into actions aimed at harm reduction in the field of drugs. From a theoretical-conceptual point of view, some of the work's categories are: Popular Education, harm reduction and social deviance. Methodologically, this is a qualitative study, with an explanatory character, and was operationalised using the ‘snowball strategy’ to map the participants and conduct semi - structured interviews. The data collected was scrutinized using Bardin's (2016) Thematic Content Analysis procedures. As a result of the analysis, five categories were formulated, which guided the discussion of the results: 1) The social movement and the school as spaces for training and encounter with Popular Education; 2) Harm reduction as an educational practice and ethical paradigm of care; 3) Popular Education in harm reduction educational practices in the area of drugs: theoretical and methodological contributions; 4) Challenges for educational work guided by Popular Education and harm reduction; 5) References in the field of popular education. Some of the results of the study show that: 1) the understanding of the educational dimension of harm reduction has a broad character, highlighting the concern with the techniques of the development of educational action and with the methods used in practice; 2) Practices guided by popular education and harm reduction prioritise elements such as participation, dialogue, valuing knowledge, joint construction of knowledge, humanisation and active listening; 3) There is limitation regarding theoretical knowledge of Popular Education, and this fact is perhaps a result of the limited availability of training opportunities in the area. In conclusion, it is pointed out, for example, the need to develop discussions both on the insertion of Popular Education in harm reduction contexts and on the type of knowledge that has been generated from practices in such contexts. It is also emphasised as essential that harm reduction experiences involving Popular Education should be systematised so that they can be studied and multiplied. Finally, the conclusion highlights the importance of reflecting on and providing training opportunities for popular educators who work with people who use drugs.